The relationship between toe-out angle during gait and progression of medial tibiofemoral osteoarthritis. Issue 10 (31st January 2007) - Chang, Alison; Hurwitz, Debra; Dunlop, Dorothy; Song, Jing; Cahue, September; Hayes, Karen; Sharma, Leena
Abstract : Background: A greater knee adduction moment increases risk of medial tibiofemoral osteoarthritis (OA) progression. Greater toe-out during gait shifts the ground reaction force vector closer to the centre of the knee, reducing the adduction moment. The present study was designed to test whether greater toe-out is associated with lower likelihood of medial OA progression. Methods: Baseline assessments included: kinematic/kinetic gait parameters using an optoelectronic camera system, force platform and inverse dynamics to calculate three-dimensional external knee moments; toe-out angle (formed by the line connecting heel strike and toe-off plantar surface centres of pressure and the forward progression line; knee pain; and full-limb alignment. Knee x -rays (semi-flexed) were obtained at baseline and at 18 months, with progression noted as medial joint space grade worsening. With logistic regression, odds ratios (ORs) for progression/5° toe-out were estimated. Results: In the 56 subjects (59% women, mean age 66.6 years, body mass index (BMI) 29), baseline toe-out angle was less in knees with than without progression (difference –4.4, 95% CI –8.5 to –0.3). Greater toe-out was associated with reduced likelihood of progression (OR 0.60, 95% CI 0.37 to 0.98). Adjusting for age, gender, BMI, pain severity and disease severity, the OR was 0.62, 95% CI 0.36 to 1.06. Adjusting for adduction moment (second peak), the OR was 0.72, 95% CI 0.40 to 1.28. Conclusions: Osteoarthritic knees that progressed had less toeing-out than knees without progression. Greater toe-out was associated with a lower likelihood of progression. Adjustment for covariates did not alter the OR, although the 95% CI included 1. Further adjustment for adduction moment did alter the OR, consistent with the possibility that a mechanism of the effect may be via lowering of the adduction moment.